Comparative genotyping of Malaysian clinical isolates of Streptococcus pneumoniae by multilocus sequence typing and multilocus variable-number tandem repeat analysis - Abdul Rahman, Nurul Asyikin; Muthanna, Abdulrahman; Mohd Desa, Mohd Nasir; Dzaraly, Nurul Diana; Hazman, Hazmin; Sulaiman, Nurshahira; Mohamad, Norfazlina; Meor Yahaya, Maitasha Alia; Al-Obaidi, Mazen M Jamil; Mohd Taib, Niazlin; Masri, Siti Norbaya; Al-Obaidi, Mazen M Jamil (Penerbit Universiti Sains Malaysia, 2025)
Background: Streptococcus pneumoniae (pneumococcus) is an opportunistic pathogen that causes severe upper and lower respiratory tract infections, leading to life-threatening diseases. This study aims to determine the genetic variation of serotypes among a collection of clinical S. pneumoniae isolates using multilocus sequence typing (MLST) and multilocus variable-number tandem repeat analysis (MLVA). Method: A total of 103 viable isolates were serotyped and subjected to MLVA; only those with discrete serotypes (n = 91) were subjected to MLST analysis. Results: The comparative phylogenetic analysis resulted in the segregation of clonal complexes (CC) and 36 singletons accordingly. The major clonal complex, MLST CC320 (n = 23; 25.3%), had a close association with the Taiwan 19F-14 clone, consisting of ST236, ST271, and ST320. The second largest group, MLST CC9 (n = 12; 13.2%), had an association with the England14-9 clone, comprising ST7 and ST9. MLVA analysis demonstrated its ability to differentiate subgroups within CCs that share the same sequence type (ST) with distinct MLVA types (MTs). Conclusion: The integration of MLST and MLVA in this study serves as a model for pneumococcal surveillance indicating some well-known globally circulating clones that have been persisting at this study setting.